Police contact and future orientation from adolescence to young adulthood: Findings from the Pathways to Desistance Study. Issue 2 (24th November 2021) - Testa, Alexander; Turney, Kristin; Jackson, Dylan B.; Jaynes, Chae M.
Abstract: In response to the changing nature of policing in the United States, and current climate of police–citizen relations, research has begun to explore the consequences of adolescent police contact for life outcomes. The current study investigates if and under what conditions police contact has repercussions for future orientation during adolescence and the transition into young adulthood. Using data from the Pathways to Desistance study, a multisite longitudinal study of serious offenders followed from adolescence to young adulthood, results from a series of fixed‐effects models demonstrated three main findings. First, personal and vicarious police contact, compared with no additional police contact, are negatively associated with within‐person changes in future orientation. Second, any exposure to police contact, regardless of how just or unjust the contact is perceived, is negatively associated with future orientation. Third, the negative association between police contact and future orientation is larger for White individuals compared with that for Black or Hispanic individuals. Considering the importance of future orientation for prosocial behavior, the findings suggest that adolescent police contact may serve as an important life‐course event with repercussions for later life outcomes.